Battery charge equalization controller in electric vehicle applications: A review - Hoque M.M.; Hannan M.A.; Mohamed A.; Ayob A. (Elsevier Ltd, 2023)
Automotive industry; Battery management systems; Controllers; Electric discharges; Electric machine control; Electric vehicles; Energy management systems; Energy storage; Environmental technology; Equalizers; Battery charge equalization; Battery energy storage systems; Battery performance; Charge and discharge; Charge equalization; Drive train; Electrochemical batteries; Vehicle applications; Secondary batteries